Preparation of iron tailings-based cementitious materials based on mechanochemical reinforcement - Li, Xuli; Zhang, Jinhui; Zhang, Yong; Ding, Siyu; Nie, Miaomiao; Li, Shefeng (Frontiers in Built Environment, 2025)
The large-scale stacking of iron tailings poses challenges to the eco-environment and mining industry. Materializing tailings treatment is an effective way to solve this bulk solid waste problem. In this study, using iron tailings rich in hematite and calcite as the main raw material, we prepared a cementitious material with about 80wt% iron tailings content by mechanical ball milling and alkali activation, with the addition of cement and slag powder. Elemental analysis of the raw materials revealed Fe, Ca, and Si contents in the iron tailings of 41.248%, 33.949%, and 20.211%, respectively, and the main mineral phases were calcite, hematite, and quartz. Our research demonstrated that mortar made from iron tailings ball-milled for 15 min exhibited the best properties, with an activity index of 108.1%. When the alkali activator content was 6%, the compressive strength of the test blocks was optimal, reaching 7.9 MPa after 28-day curing. We also conducted tests on standard consistency, setting time, and hydraulic properties, confirming the potential activity of iron tailings. Using orthogonal experiments, we optimized the proportions of each component and explored the effects of tailings content and water - binder ratio on the mechanical properties of the samples. Furthermore, we analyzed the microstructure of the cementitious material with different tailings contents and curing ages using FTIR and XRD and proposed its hydration mechanism.